Correlation between the formation of tribofilm and repassivation in biomedical titanium alloys during tribocorrosion. (November 2021) - Xu, Yidong; Qi, Jiahui; Nutter, John; Sharp, Joanne; Bai, Mingwen; Ma, Le; Rainforth, W.M.
Abstract: Titanium alloys are widely used in the field of orthopaedics, however, poor tribological performance arising from the low shear resistance and weak protection of the oxide layer limits their applicability. In this work, the tribocorrosion behaviour of novel β and α + β biomedical titanium alloys were studied in bovine serum solution under open circuit potential. Ti-5Mo-Fe-3Sn and Ti-6Al-4V ELI alloys were found to have the capability to repassivate when testing at a slower sliding speed. Scanning and transmission electron microscopy results revealed that the repassivation was mainly associated with the greater tribofilm formation on the worn surface, rather than an oxide film. The tribolayer performed as a solid lubricating film, which stabilised the coefficient of friction. Graphical Abstract: ga1 Highlights: Ti-5Mo-Fe-3Sn alloy exhibited better corrosion resistance and tribocorrosion behaviour. Decreasing the sliding speed resulted in unstable repassivation in both Ti-5Mo-Fe-3Sn and Ti-6Al-4V ELI. Wear debris led to further ploughing and thereby the destruction of the passive state. The effect of tribofilm formation on wear resistance and subsurface microstructure is revealed.